2022
DOI: 10.3390/en15197281
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Fuel Additives and Their Spray Characteristics for Diesel-Based Blends

Abstract: The spray characteristics play a crucial role in determining the performance and emissions of compression ignition (CI) engines at the pre-combustion stage. With the advent of many types of alternative fuels and their blends with diesel, it is necessary to investigate the effect of fuel properties and various injection conditions to determine the penetration length, spray cone angle and spray area for a viable fuel with similar or better dispersion characteristics to diesel. Hence, this study reviews and summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…In parallel, the improvement of biodiesel production, in order to make this process as competitive as possible compared to petrol-based refineries, has gained attention from researchers from many fields. Thus, the use of different catalysts (both homogeneous and heterogeneous) [6], feedstocks (including microalgae) [7] or additives [8] to improve the performance of biodiesel, among other things, have been popular topics of research.…”
Section: Introduction 1the Role Of Biodiesel In Global Energy Scenariomentioning
confidence: 99%
“…In parallel, the improvement of biodiesel production, in order to make this process as competitive as possible compared to petrol-based refineries, has gained attention from researchers from many fields. Thus, the use of different catalysts (both homogeneous and heterogeneous) [6], feedstocks (including microalgae) [7] or additives [8] to improve the performance of biodiesel, among other things, have been popular topics of research.…”
Section: Introduction 1the Role Of Biodiesel In Global Energy Scenariomentioning
confidence: 99%
“…The ignition-delay time refers to the time interval between the start of fuel injection or the introduction of an ignition source and the onset of visible combustion. A constant-volume chamber alongside a rapid compression machine (RCM) or a shock tube, is typically used for ignition-delay measurements [19]. These chambers provide controlled conditions and allow for the precise measurements of the ignition-delay time.…”
Section: Experimental Analysis Of Combustionmentioning
confidence: 99%
“…Diesel can be blended with oxygenated additives like alcohols or ethers to obtain desirable results [15,16]. These additives reduce the viscosity of the biodiesel blend and may also reduce emissions in a diesel engine when blended with biodiesel [17][18][19]. In most cases, utilizing biodiesel with or without diesel reduces the engine performance by increasing brake-specific fuel consumption and decreasing brake thermal efficiency [20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, none of the mentioned literature has presented smoke emissions data. Some of the recent and relevant review papers for biodiesel-based blends with NP additives are by Lv et al [47], Haq et al [48], and Ampah et al [49]. Lv et al [47] reviewed the effects of nano-additives added to diesel-biodiesel fuel blends on combustion and emission characteristics of diesel engines.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various studies in their review mention that adding cerium oxide or ceria nanoparticles to diesel–biodiesel fuel blends can improve combustion and reduce emissions to varying degrees. Haq et al [ 48 ] reviewed fuel additives, including nano-additives and their spray characteristics, for diesel-based fuel blends. They confirmed that cerium oxide nanoparticles have high surface/volume ratio and cause improvement in chain reactions during combustion.…”
Section: Introductionmentioning
confidence: 99%